Rancang Bangun Smart Box Untuk Penyimpanan Paket Menggunakan Arduino Nano Dan Esp32-Cam Berbasis Internet Of Things - Riezqi, Adri Dzaki Fateha; Saputra, Herlambang; Sutrisman, Adi (Teknik Komputer Politeknik Negeri Sriwijaya, 2025)
With the increasing volume of online shopping, the need for a secure and reliable package storage system has become more critical. To address issues such as loss, damage, and failed deliveries due to the recipient's absence, a Smart Box system based on the Internet of Things (IoT) was designed using an Arduino Nano microcontroller and an ESP32-CAM module. This system enables automatic locking and unlocking of the box through barcode scanning and is equipped with a camera to document the package reception process. The ESP32-CAM module also sends notifications and images to the package owner via a Telegram bot. Test results show that the system can accurately read barcodes and successfully send photos and notifications through Telegram. It can be concluded that this IoT-based Smart Box is secure and feasible to be implemented as a solution to enhance the safety and autonomous management of package storage.